Web-Based Design and Construction of HMI Member Registration for Prabumulih City - Krisna; Ariansyah; Nurmayanti (Yayasan Kita Menulis, 2026)
The Islamic Students Association (HMI) Prabumulih Branch still carries out its member registration process conventionally, such as using physical forms and manual data collection, which can lead to delays and disorganized data management. This study aims to design and develop a web-based member registration system that simplifies administrative processes and improves committee work efficiency. The system development methodology used in this study is the Waterfall method, which includes requirement analysis, system design, implementation, testing, and maintenance. The result of this research is a web-based registration system that can be accessed online by prospective members and the organizing committee, featuring digital form filling, document uploads, and member data management. This system is expected to support a more structured, efficient, and modern registration process within the HMI Prabumulih Branch organization.